Determining Students' Views about an Educational Game-Based Mobile Application Supported with Sensors - ÖZDENER DÖNMEZ, NESRİN (SPRINGER, 2019)
The use of mobile applications which are developed for smartphones and tablets is increasing. They use special features of the devices such as integrated cameras, geopositioning, and location and orientation sensors. The purpose of this study is to examine students' opinions on using an educational mobile application which is supported by sensors as a homework tool. In the scope of the study, we have examined the students' opinions regarding the usage of sensors in mobile applications, their ideas on the usage of mobile applications for homework, and mobile applications' scorekeeping feature. The overall findings indicated that most of the students preferred to use mobile applications with sensors and the sensor feature was the first thing they mentioned when they were asked to compare two mobile applications. In addition, almost all of the students stated that they would like to use mobile games for homework. All of the students stated that they like the highest score feature and they said that they enjoyed trying to beat their highest scores. Most students also reported that they liked to look at their friends' highest scores.
Keywords: Mobile learning; Smartphones; Sensor; Educational mobile game; COMPETITION; MOTIVATION; ENGAGEMENT